Damage to mitochondrial DNA induced by the hepatocarcinogen diethylnitrosamine in ovo - Enzmann, Harald G.; Kühlem, C.; Löser, Eckhard; Bannasch, Peter (Mutation research. Fundamental and molecular mechanisms of mutagenesis, 1995)
Different doses of the hepatocarcinogen diethylnitrosamine (DEN) were injected into fertilized turkey eggs 8 days before hatching. The embryos were removed from teh eggs after 4 days and liver samples were shock frozen. Mitochondrial DNA (mtDNA) was purified from the samples. Electrophoresis on agarose gels with native mitochondrial DNA and with ribonuclease-treated mitochondrial DNA revealed a DEN-induced effect on the molecular size of the mtDNA. The content of mtDNA of the regular size of 16 kb dose-dependently decreased, whereas the amount of mtDNA fragments of various size increased. Fluorescent staining of the electrophoresis gels allowed the densitometric quantification of the mitochondrial DNA of the regular band at 16 kb and the amount of fragments of irregular size (smear). The diethylnitrosamine-induced effect was dose-dependent over the whole dose range from 1.24 to 6.2 mmol/kg. Even the lowest dose (10 mg DEN per egg) showed clear-cut effects. Mitochondrial damage and malfunction may be mechanistically involved in the neoplastic transformation and in aging phenomena. The in ovo model is a simple and rapid approach for investigations on chemically induced alterations of mtDNA.